A Caliber Persistent Artery (Dieulafoy’s Lesion) which is Associated with an Early-Stage Gastric Stump Cancer Following a Distal Gastrectomy - Simona Gurzu; Constantin Copotoiu; Leonard Azamfirei; Ioan Jung (Journal of Clinical and Diagnostic Research, 2013)
A 75–years old man was hospitalized with symptoms which suggested gastric cancer. Thirty-eight years ago, he had undergone a Billroth-II gastric reconstruction for a peptic ulcer. At the present admission, he had presented with an eight-month history of recurrent haematemesis, epigastric pain, vomiting, and fatigue. The emergent endoscopy showed a type 0-IIc (superficial depressed) early gastric stump cancer in the anastomotic area and total removal of the gastric remnant and the jejunal segment was performed. The histological examination of the surgical specimen showed a gastric adenocarcinoma that invaded the mucosa and the submucosa, without lymph node metastases (pT1bN0 stage). Besides the tumour, enlarged vessels were observed in the submucosa and the muscularis propria, some of which were thrombotic. The surrounding normal gastric wall also presented submucosal oversized vascular spaces, some of which were protruding through the muscularis mucosae in the mucosal layer. Based on these characteristics and the recurrent haematemesis, a final diagnosis of early gastric stump carcinoma which was associated with Dieulafoy’s lesion was made. This association has not yet been reported in the literature and it allowed us to diagnose the gastric stump cancer in a very early stage.